A Novel Cardiomyocyte-enriched MicroRNA, miR-378, Targets Insulin-like Growth Factor 1 Receptor: IMPLICATIONS IN POSTNATAL CARDIAC REMODELING AND CELL SURVIVAL - Knezevic, Ivana (American Society for Biochemistry and Molecular Biology, 2012)
Postnatal cardiac remodeling is characterized by a marked decrease in the insulin-like growth factor 1 (IGF1) and IGF1 receptor (IGF1R) expression. The underlying mechanism remains unexplored. This study examined the role of microRNAs in postnatal cardiac remodeling. By expression profiling, we observed a 10-fold increase in miR-378 expression in 1-week-old neonatal mouse hearts compared with 16-day-old fetal hearts. There was also a 4–6-fold induction in expression of miR-378 in older (10 months) compared with younger (1 month) hearts. Interestingly, tissue distribution analysis identified miR-378 to be highly abundant in heart and skeletal muscles. In the heart, specific expression was observed in cardiac myocytes, which was inducible by a variety of stressors. Overexpression of miR-378 enhanced apoptosis of cardiomyocytes by direct targeting of IGF1R and reduced signaling in Akt cascade. The inhibition of miR-378 by its anti-miR protected cardiomyocytes against H(2)O(2) and hypoxia reoxygenation-induced cell death by promoting IGF1R expression and downstream Akt signaling cascade. Additionally, our data show that miR-378 expression is inhibited by IGF1 in cardiomyocytes. In tissues such as fibroblasts and fetal hearts, where IGF1 levels are high, we found either absent or significantly low miR-378 levels, suggesting an inverse relationship between these two factors. Our study identifies miR-378 as a new cardioabundant microRNA that targets IGF1R. We also demonstrate the existence of a negative feedback loop between miR-378, IGF1R, and IGF1 that is associated with postnatal cardiac remodeling and with the regulation of cardiomyocyte survival during stress.